Karl Leonhard (1904–88) and his academic influence through the 'Erlangen School'. Issue 2 (June 2021) - Braun, Birgit
The Erlangen University Psychiatric and Mental Clinic was an annexe to the Erlangen Mental Asylum, so when Leonhard worked there he became acquainted with acute and chronic stages of schizophrenia. This can be viewed as a decisive impulse for his later differentiated classification of types of schizophrenia. The suspicion that Leonhard suffered from attention deficit hyperactivity disorder cannot be supported. His reticence concerning social-psychiatric aspects is analysed in the context of his early professional contact with the 'Erlangen system' of open care and its Nazi perversion. Leonhard's role in National Socialism is still uncertain. His unsuccessful attempts to retain the Erlangen Chair of Psychiatry and Mental Illness in 1951 can be viewed as his first difficulty in the tensions between West Germany and East Germany.